The consequences of work‐family conflict and the importance of social supports to reduce work‐family conflict among employees - Zakaria, Noorfadhila; Ismail, Zanariah (Secholian Publication PLT, 2017)
Conflicts that occur due to overlap between work and family matters are important topics in today’s organizational context. Work-family conflict can be defined as a form of role conflict where the demands of work and family cannot be aligned in several ways. Some previous studies have mentioned that work-family conflicts negatively affect individuals such as emotional fatigue that ultimately lead to stress and disturb the psychological well-being. From that perspective, social support can help to reduce the stressful experience that is caused by work-family conflicts and improve the psychological well-being. There are two elements of social support originating from (1) work domain support; such as organization, supervisor and co-workers whereas, (2) non-work domain supports: can come from spouse, family members and friends. Thus, these two elements of social support seemed to be important elements to ease the burden of stressful experience among employees especially in work- family conflict.